Comparing Central Aortic Pressures Obtained Using a SphygmoCor Device to Pressures Obtained Using a Pressure Catheter. (25th January 2022) - Esposito, Cara; Machado, Priscilla; Cohen, Ira S; Mehrotra, Praveen; Savage, Michael; Fischman, David; Davis, Marguerite; Ruggiero, Nicholas; Walinsky, Paul; McDonald, Maureen E; Dickie, Kristopher; Forsberg, Flemming; et al.
Abstract: BACKGROUND: This study compared aortic pressures estimated using a SphygmoCor XCEL PWA device (ATCOR, Naperville, IL) noninvasively with aortic pressures obtained using pressure catheters during catheterization procedures and analyzed the impact of a linear-fit function on the estimated pressure values. METHODS: One hundred and thirty-six patients scheduled for cardiac catheterization procedure were enrolled in IRB approved studies. Catheterization procedures were performed according to standard-of-care to acquire aortic pressure measurements. Immediately after the catheterization procedure with the pressure catheters removed, while the patients were still in the catheterization laboratory, central aortic pressures were estimated with the SphygmoCor device (using its inbuilt transfer function). The error between measured and estimated aortic pressures was evaluated using Bland–Altman analysis ( n = 93). A linear-fit was performed between the measured and estimated pressures, and using the linear equation the error measurements were repeated. A bootstrap analysis was performed to test the generalizability of the linear-fit function. In a subset of cases ( n = 13), central aortic pressure values were also obtained using solid-state high-fidelity catheters (Millar, Houston, TX), and the error measurements were repeated. RESULTS: The magnitude of errors between the measured and estimated aortic pressures (mean errors >6.4 mm Hg; mean errors >8.0 mm Hg in the subset) were reduced to less than 1 mm Hg after using the linear-fit function derived in this study. CONCLUSIONS: For the population examined in this study, the SphygmoCor data must be used with the linear-fit function to obtain aortic pressures that are comparable to the measurements obtained using pressure catheters. CLINICAL TRIALS REGISTRATION: Trial Numbers NCT03243942 and NCT03245255. Graphical Abstract: